Managing standards in corporate social responsibility online: a case study of a Malaysian higher learning institution - Mohd Hassan, Nurul` Ain (Serials Publications, 2017)
The purpose of this study is to explore the current standards of Corporate Social Responsibility (CSR) initiatives through the lens of a public university's official corporate website with the aim to see which areas of CSR are addressed when measured against a set of existing and accepted best practice standards for developing nations. A case study approach was utilised to investigate a local Malaysian public university using a qualitative content analysis method. The data suggests that managing the university's corporate website is incomprehensive particularly in the areas of human rights and anti-corruption areas. The main focus was on community driven area. This study provides a platform for further investigation to explore the trend of the current practice of CSR initiatives in Malaysian higher education institutions.